PENGEMBANGAN INSTRUMEN MEDIA PEMBELAJARAN BERBASIS POWER POINT DI TK AM KABUPATEN SEMARANG - Santoso, Didik Ardi; Wirahno, Dewi Nugrahastuti; Sahrul, Sahrul (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2022)
An instrument used to gather data for research is called a research instrument. It is crucial to choose appropriate instrument types in order to ensure that the data obtained from the study is valid and relevant to the study's objectives. Perancangan, pembuatan, pengujian, and penyempurnaan alat ukur that are used to gather data for research are known as research instrument development. A good instrument should have high validity and reliability, which means that they are able to accurately determine what needs to be checked and produce consistent data when used in different conditions. The study's findings indicate that two instruments—the uji ahli and the ceklis instrument at TK AM Kabupaten Semarang—can be analyzed to assess their validity and reliability. The subject of the study is the power point learning instrument. The purpose of this study is to determine whether the powerpoint-based data pernyataan instrument created by the researcher is legitimate and can be compared with 60 subjects from grades A-1, B-1, and C-1, each of whom has 20 children. The study's findings were based on a statistical analysis of the data conducted using the Jamovi application (version 2.4.14). The results of the instrument's lapangan uji on the subject have a nilai that is closer to 0.3, indicating that the instrument is legitimate. Table 1 presents the results of the analysis of the correlation coefficient of 0.805, while Table 2 presents the validity check with a value of 0.3. In addition, because the terms Instrument, Media, and Power Point are not used in the city that is being warned about, Heatmap korelasi indicates that relationships are still categorized in a high degree. Kata Kunci: Media, Power Point, and Instruments